Pre-treatment with compound Danshen dripping pills prevents lipid infusion-induced microvascular dysfunction in mice. (1st January 2020) - Zhang, Yanda; Zhao, Jian; Ding, Ru; Niu, Wenhao; He, Zhiqing; Liang, Chun
Abstract: Context: Recent studies have shown compound Danshen dripping pills (CDDP) could improve microcirculation in ischemic/reperfusion injury and other microvascular disorders. The mechanism for CDDP's role in microcirculation is not clear. Objective: To explore the protective effects of CDDP on microvascular dysfunction. Materials and methods: C57BL/6 male mice (6–8 weeks) were randomized into control, model and CDDP groups ( n = 10), which were treated with normal saline or CDDP (105.30 mg/kg), respectively. Then, lipid emulsion and heparin were infused via mice jugular vein to establish systemic microvascular dysfunction model. Coronary flow reserve (CFR) and leukocytes adhesion on microvascular wall were measured. Relative CD11b and CD62L expression levels on neutrophils were measured by flow cytometric analysis. Expression level of forkhead box transcription factor O1 (FOXO1) mRNA was identified by real-time PCR. Results: Lipid infusion significantly attenuated the CFR (1.84 ± 0.14 vs. 2.65 ± 0.02) and increased the number of leukocytes adherent to microvascular wall in cremaster (4067.00 ± 581.20 cells/mm 2 vs. 10.67 ± 4.81 cells/mm 2 ). The expression level of CD11b and FOXO1 in neutrophils was also up-regulated by lipid infusion. Pre-treatment with CDDP significantly improved CFR (2.57 ± 0.29 vs. 1.84 ± 0.14), decreased the number of leukocytes adherent to microvascular wall (2500.00 ± 288.70 cells/mm 2 vs. 4067.00 ± 581.20 cells/mm 2 ) and down-regulated CD11b and FOXO1 expression. Discussion and conclusions: Pre-treatment with CDDP could prevent lipid infusion-induced systemic microvascular disorder including coronary and peripheral microvascular dysfunction. Down-regulated FOXO1 and decreased leukocyte adhesion might play an important role in the mechanisms of CDDP's efficacy.